Synthesis of New-2,3-Disubstituted Quinoxaline - Kolhe, S.V.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
2-α Dibromo-2-(substituted benzyl)-3-nitro-5-chloro coumaran-3-one (1a–p) in methanol condensed with benzene-1,2-diamine in presence of few drops of concentrated H2SO4 affords 2,3-disubstituted quinoxalin (IIa–p). The structural elucidation of compounds were done on the basis of analytical and spectral data.